2016
DOI: 10.1038/cr.2016.58
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of Zika virus targeting the radial glial cells affects cortex development of offspring mice

Abstract: The recent Zika virus (ZIKV) epidemic in Latin America coincided with a marked increase in microcephaly in newborns. However, the causal link between maternal ZIKV infection and malformation of the fetal brain has not been firmly established. Here we show a vertical transmission of ZIKV in mice and a marked effect on fetal brain development. We found that intraperitoneal (i.p.) injection of a contemporary ZIKV strain in pregnant mice led to the infection of radial glia cells (RGs) of dorsal ventricular zone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
261
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(309 citation statements)
references
References 38 publications
22
261
3
3
Order By: Relevance
“…[6][7][8][9] Three of the studies introduced different ZIKV strains into pregnant mice through peripheral inoculation routes (intravenous, intraperitoneal, or subcutaneous), 6,7,9 and two studies inoculated ZIKV directly into the fetal brain. 8,9 All the studies established ZIKV infection in fetuses with resultant injury to cells in the central nervous system; one study showed the cellular basis of transmission of ZIKV from maternal blood to the fetus.…”
Section: L I N I C a L I M P L I C A T I O N S O F B A S I C R E S mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Three of the studies introduced different ZIKV strains into pregnant mice through peripheral inoculation routes (intravenous, intraperitoneal, or subcutaneous), 6,7,9 and two studies inoculated ZIKV directly into the fetal brain. 8,9 All the studies established ZIKV infection in fetuses with resultant injury to cells in the central nervous system; one study showed the cellular basis of transmission of ZIKV from maternal blood to the fetus.…”
Section: L I N I C a L I M P L I C A T I O N S O F B A S I C R E S mentioning
confidence: 99%
“…In addition, this group noted ocular abnormalities that were similar to those that have been described in humans. 11 Li et al 8 and Wu et al 9 injected contemporary Asian ZIKV strains directly into the lateral left ventricle of fetal brains at E13.5 (equivalent to the late second trimester of pregnancy in humans) and analyzed tissues before 8 or after 9 birth. Both groups observed a reduction in the number of cortical neural progenitors in the dorsal ventricular and subventricular zones, and this loss was associated with cell death.…”
Section: L I N I C a L I M P L I C A T I O N S O F B A S I C R E S mentioning
confidence: 99%
“…Recent evidence, derived with animal models, has suggested that the virus is transmitted to the fetus across the placenta. Although the exact mechanism by which the virus crosses the placental membrane is uncertain, it has been hypothesized that the virus crosses from the maternal bloodstream in the chorionic villi to the placenta, where it is amplified before spreading into the fetal circulation and moving to infect neural progenitor cells (NPCs) (Miner et al, 2016;Quicke et al, 2016;Silva & Souza, 2016;Wu et al, 2016).…”
Section: Exposurementioning
confidence: 99%
“…Cugola and colleagues 40 administered ZIKV to pregnant mice in midgestation and produced some animals with stunted heads, intrauterine growth restriction, and ocular abnormalities. Wu et al 41 performed intraperitoneal inoculation of pregnant mice with ZIKV, producing viremia, placental infection, and subsequent viral infection of the radial glial cells of the dorsal ventricular zone of the fetal brain. This reduced the number of radial glial cells, the primary neural cells responsible for the development of the cortex, and consequently, decreased the surface area of the cortex and the lateral ventricles.…”
Section: Experimental Infection Neurotropism Andmentioning
confidence: 99%